The Development of Islamic Education: An Analysis of Hasan al-Banna's Thought - Yunus Dumbe; Jibrail Bin Yusuf; Gamal Abdul Nasir Zakaria; Shazia Malik; Saiful Anwar; Guntur Cahyono; Moch.Charis Hidayat (CV. Zamron Pressindo, 2024)
Research Objective– This study aims to analyze Hasan al-Banna's perspective on the development of Islamic education, focusing on the integration of intellectual, spiritual, and physical growth within education, rooted in the values of the Qur'an and Sunnah. Methodology– This research employs a library research method with a descriptive-analytical approach. Data were collected from books, journals, and other relevant literature, then analyzed qualitatively to explore Hasan al-Banna's ideas on Islamic education. Findings– The study reveals that Hasan al-Banna proposed the concept of al-tarbiyah as a holistic educational process encompassing moral, spiritual, and skill-based education. He emphasized the importance of a strong foundation for Islamic education based on the Qur'an and Sunnah and advocated adaptive educational methods that not only transfer knowledge but also shape the character of individuals to become shalih (righteous) and mushlih (positively contributing to society). Research Implications/Limitations– The findings have significant implications for the development of contemporary Islamic education, particularly in integrating Islamic educational values with modern societal needs. However, this study is limited to theoretical analysis without direct empirical research. Originality/Value– This research provides an original contribution by offering a holistic Islamic educational framework based on Hasan al-Banna's thought. His ideas remain relevant for fostering a generation that is faithful, knowledgeable, and positively impactful in the modern era.